Impact of Plant Root Morphology on Rooted-Soil Shear Resistance Using Triaxial Testing - Suyun Meng; Guoqing Zhao; Yuyou Yang (Advances in Civil Engineering)
Mechanical reinforcement by plant roots increases the soil shearing strength. The geometric and distribution characteristics of plant roots affect the soil shearing strength. Current research on the shear strength of rooted-soil is mostly based on direct shear tests with a fixed shear surface and thus cannot reflect the actual failure state of the rooted-soil. In this study, Golden Vicary Privet was used to create a rooted-soil, and a triaxial test method was used for soil mechanical property analysis. The influence of the root geometry (root diameter and individual root length) and distribution characteristics (root density and root distribution angle) on the rooted-soil shearing strength was studied by controlling the root morphology in the specimens. According to the results, both the root geometry and distribution characteristics affect the rooted-soil shearing strength. For a fixed total length of the roots, the longer the individual root length is, the better the soil shearing strength is. In addition, the reinforcement effect of the root system increases as the angle between the root and the potential failure surface increases. The results also show that the root system significantly enhances the soil cohesion while only minimally affecting the internal friction angle. The maximum rooted-soil cohesion is 2.39 times that of the plain soil cohesion, and the maximum internal friction angle of rooted-soil is 1.24 times that of plain soil. This paper provides an approach for the determination of the rooted-soil strength and a rationale for vegetation selection in ecological slope reinforcement applications.